Significance and Correlation of Lupus Anticoagulant and Anticardiolipin Antibody Assay in High-risk Pregnancy - Blessy Mathew; Beenu Singh; Gurpreet Kaur; Metaanksha Ahuja; Ahuja Ankur; Gahlot P. S. Gaurav (Journal of Marine Medical Society)
Background: Antiphospholipid antibodies (aPL), a heterogeneous group of circulating antibodies including lupus anticoagulant (LAC), anticardiolipin antibodies (aCL), & anti-beta-2-glycoprotein 1 antibodies (aβ2GP1) that have been associated with increased risks for thrombosis and adverse obstetric outcomes. Aims and Objectives: The lupus anticoagulant tests have variable sensitivity of different clot-based assays i.e. aPTT-LA and dRVVT. The utility & comparison of each lupus anticoagulant assay will be analyzed in high-risk pregnancy clinics. Materials and Methods: This retrospective and prospective observational study was conducted over 200 high risk pregnancy cases from Nov 2017 to Jan 2018 at a tertiary care Armed Forces Institute. Equal number of high risk pregnancy cases as patients & normal antenatal patients matched for age as controls were included. 10 ml venous blood collected in tubes in a 9:1 ratio of blood to 3.2% trisodium citrate solution for lupus anticoagulant assay & 3 ml venous sample collected in serum vacutainer for anticardiolipin antibody assays. The STA-Staclot dRVV Screen and STA-Staclot dRVV Confirm kits were used for the detection of lupus anticoagulants in the plasma of patients. The Chi square test & results were analyzed using SPSS version 20. Results: A statistically significant positive association between history of IUGR with aCL IgG/IgM antibodies (p-value 0.008) and an insignificant association with the LAC assay was observed. Conclusion: Using both aPTT-LA & dRVVT tests as per ISTH recommendation resulted in more prevalence of LAC (24.6%).